Three-Timescale Hierarchical Multi-Objective Volt/Var Control in Active Distribution Network With Inverters Droop Control - Meiyi Liu; Hsiao-Dong Chiang; Tengmu Li (IEEE Access)
In response to the uncertainties and power quality degradation caused by the integration of numerous renewable energy resources (RESs) and the increasing adoption of plug-in electric vehicles (PEVs) in active distribution networks (ADNs), this paper proposes a three-timescale hierarchical volt/var control (VVC) model operating at 1 hour, 15 minutes, and 1 minute. The model aims to achieve effective coordination between centralized optimization and local control, considering the unique characteristics of different reactive power control devices. A three-stage optimization method is developed to solve the proposed three-timescale models; specifically, a three-step method is proposed to solve the one-hour look-ahead model for scheduling the tap position of the on-load tap changer (OLTC) and the number of switching groups for the shunt capacitors (SCs). For the 15-minute timescale, the voltage set-point of the inverter is optimized to minimize the voltage deviations of the pilot buses in typical scenarios, taking into account the uncertainties associated with RESs. For the 1-minute timescale, local measurement information is utilized, and a double-loop droop control method is adopted to track the voltage setting value provided by the 15-minute timescale model. This ensures the optimization of the system’s voltage level and the minimization of voltage fluctuations. The IEEE 33-bus and IEEE 123-bus distribution networks are employed to validate the proposed method and its ability to deal with uncertainties.